A recipe of surfactant for the flotation of fine cassiterite particles. (1st January 2021) - Chen, Yumeng; Li, Hua; Feng, Dongxia; Tong, Xiong; Hu, Shunxuan; Yang, Fan; Wang, Guichao
Graphical abstract: Highlights: Cassiterite exhibited 10% higher floatability in presence of AT compared to MIBC. AT increased synergistically with SHA the hydrophobicity of cassiterite particles. The surface tension of SHA/AT solution was lower than that of SHA/MIBC solution. The combined effects worked towards to the advantages of cassiterite flotation. Abstract: Salicylhydroxamic acid (SHA) has been widely used as collector in cassiterite flotation, and α-terpineol (AT) and methyl isobutyl carbinol (MIBC) are common frothers in mineral flotation. The effects of AT and MIBC on cassiterite flotation have rarely been reported, which severely limits our understandings of the role of frother in cassiterite flotation. Here, comparative studies between AT and MIBC in affecting cassiterite flotation using SHA as collector were conducted through micro-flotation tests. Micro-flotation tests showed that the averaged value of the recovery of cassiterite with AT was 10% higher than that with MIBC at the same concentration. To unveil the mechanisms of enhancement effects of AT on the flotation of fine cassiterite particles, zeta potential measurements, contact angle measurements and surface tension measurements were conducted. Zeta potential of cassiterite surface shifted to more negative value in the presence of SHA, and the nonionic reagents, AT and MIBC, could not affect the surface potential of cassiterite. Contact angle measurements showed AT could adsorb on the surfaces of cassiterite particles, and therefore the hydrophobicity of particles was increased. In addition, there was a synergistic behavior between SHA and AT on cassiterite surface due to co-adsorption, and the cassiterite surface was more hydrophobic in the SHA/AT solution. Less surface tension and smaller bubble size were obtained in the SHA/AT solution compared to SHA/MIBC solution. These two combining effects, i.e. increasing the hydrophobicity of cassiterite particles and reducing the single bubble size, are beneficial to the flotation of cassiterite, which explains higher recoveries in cassiterite flotation when AT is used as frother and SHA as collector.